Integration between the public authorities and universities in popularization of knowledge concerning biodiversity - Castellari, Rafael Ramos; Smith, Welber Senteio (Revista Brasileira de Educação Ambiental (RevBEA), 2015)
Abstract: Brazil is one of the countries with the greatest biodiversity on the planet, housing between 15 and 20% of the total number of species. Some of that wealth has been inexorably lost, therefore it is necessary to know in depth the natural heritage of the country, to identify the main factors that threaten them and set priorities for action. Knowledge, supported by scientific rigor, is a powerful tool to permanently engage the action of the public authorities in the planning and conservation which, consequently, may introduce more effective instruments of control, supervision and protection process. The Secretary of Environment, in order to subsidize and provide guidelines for environmental actions within the city, articulated with institutions and researchers, during the year of 2013, the theme “Biodiversidade do Município de Sorocaba” [“Biodiversity of the city of Sorocaba”], which resulted in two products published in the official newspaper of the city and a book). These represent important mechanisms that subsidize conservation efforts and environmental education.Keywords: Conservation; Municipality; Urban Ecosystems.Resumo: O Brasil é um dos países com a maior diversidade biológica do planeta, abrigando entre 15 e 20% do número total de espécies. Parte dessa riqueza tem sido perdida de forma inexorável, portanto, é necessário conhecer com mais profundidade o patrimônio natural do país, identificar os principais fatores que os ameaçam e estabelecer prioridades de ação. O conhecimento, respaldado no rigor científico, constitui instrumento poderoso para envolver de forma definitiva a ação do poder público no processo de planejamento e conservação que, assim, podem instituir instrumentos de controle, fiscalização e proteção mais eficazes. A Secretaria Municipal do Meio Ambiente de Sorocaba, com o objetivo de subsidiar e dar diretrizes às ações ambientais, no âmbito do município, articulou junto a instituições e pesquisadores, durante o ano de 2013, o tema “Biodiversidade do Município de Sorocaba” o que culminou em dois produtos (publicação no diário oficial do município e um livro) sendo estes importantes mecanismos que subsidiarão ações de conservação e educação ambiental.Palavras-chave: Conservação; Municipalidade, Ecossistemas Urbanos.